Društveno-historijska valorizacija značaja prvog zasjedanja ZAVNOBIH-a / Social-Historical Importance Valorization of the First Session of ZAVNOBIH - Londrc, Benjamina (Pregled: časopis za društvena pitanja / Periodical for social issues, 2020)
Text is the review of Proceedings "75th Anniversary of ZAVNOBIH: Historical Foundation of Restored Statehood of Bosnia and Herzegovina in 20th and 21st century", Academy of Science and Arts of Bosnia and Herzegovina, Sarajevo, 2019.